FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN MINAT WUS MELAKUKAN DETEKSI DINI KANKER LEHER RAHIM DI PUSKESMAS TANJUNG MARULAK KOTA TEBING TINGGI TAHUN 2017 - Rinawati Sembiring; Idaria Sidabukke; Juniati Riana Malan (UNIVERSITAS SARI MUTIARA INDONESIA, 2017)
Reproductive health problems faced by women at this time was the increasing infection of the reproductive organs, which ultimately cause cancer. One of the diseases that can interfere with the health of the female reproductive organ is the cervical cancer is the cancer most often strikes women around the world.The purpose of this research is to know the factors that relate to interest WUS do early detection of cervical cancer in the clinic of Cape Town High Marulak Cliff-2017. The type of research conducted with the analytic study is cross-sectional. Research conducted at health centers in Cape Town Marulak high cliff.This research population is WUS Marulak City health centers in high cliffs that have been married asmany as 250 people and as many as 71 samples of respondents. Research results retrieved 1) there is a relationship of parity with the WUS interest do the early detection of cervical cancer (p = 0.05);2) there is a connection with an interest in knowledge WUS do early detection of cervical cancer (p = 0.000);3) no relationship with contraception usage WUS interest do the early detection of cervical cancer (p = 0.875);4) no relationship history of smoking with WUS interest do the early detection of cervical cancer (p = 0.185); 5) not having sex at a young age with an interest in WUS do early detection of cervical cancer (p = 0.061). From the results it can be concluded that there is a relationship of age, education, parity, attitude and knowledge interests WUS do early detection of cancers of the neck and no relationship contraception usage, history of smoking and do sexual at a young age with an interest in doing the early detection of cervical cancer. From these results it is recommended that Puskesmas Tanjung Marulak Kota Tebing Tinggi increase health education activities about early detection of cervical cancer to the WUS through counseling or a direct home-home of engage WUS to do early detection of cancer of the neck while for WUS to do early detection of cervical cancer